2019
DOI: 10.3390/su11185043
|View full text |Cite
|
Sign up to set email alerts
|

Alien Plants in the Eastern Cape Province in South Africa: Perceptions of Their Contributions to Livelihoods of Local Communities

Abstract: Invasive alien plant species are plant species that establish themselves outside their native distributional range. The current study documented utilization of alien plant species in the Eastern Cape province in South Africa. Information about utilization of alien plant species was gathered through interviews conducted with 120 participants, which included 13 traditional healers, 27 herbalists, ten farmers and 70 laypeople. Ethnobotanical importance of documented species was assessed through evaluation of use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 70 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…Uprety et al (2012) argued that documentation and conservation of wild edible plants are important as this would ensure that the highest priority genetic diversity is preserved and made available for use in crop improvement programs as a contribution to future worldwide food security. Moreover, documenting such information on utilization of plant species based on perceptions of local communities is an important step in trying to understand and initiate a management protocol that incorporates public perceptions and values associated with utilization of plant resources (Atyosi et al, 2019). In conclusion, results of this study have added invaluable information on edible vegetable species in the Eastern Cape Province in South Africa.…”
Section: Edible Partsmentioning
confidence: 90%
“…Uprety et al (2012) argued that documentation and conservation of wild edible plants are important as this would ensure that the highest priority genetic diversity is preserved and made available for use in crop improvement programs as a contribution to future worldwide food security. Moreover, documenting such information on utilization of plant species based on perceptions of local communities is an important step in trying to understand and initiate a management protocol that incorporates public perceptions and values associated with utilization of plant resources (Atyosi et al, 2019). In conclusion, results of this study have added invaluable information on edible vegetable species in the Eastern Cape Province in South Africa.…”
Section: Edible Partsmentioning
confidence: 90%
“…Some IAPs are utilised as traditional leafy vegetables owing to their nutritional value, thus making a significant contribution to human well-being [122][123][124]. In southern parts of Nigeria, C. odorata leaves are consumed as a vegetable, and this is largely attributed to high nutritional content in the leaves [41].…”
Section: Food Sourcementioning
confidence: 99%
“…The research showed that the main invasive plants in Zhejiang Province were herbs, which grow fast and have strong reproductive capacity [24]. Alien species were often considered to have a negative impact on local biodiversity, but research showed that interaction with alien species was neutral or even promoted native species [25], and alien species were even more dynamic and competitive than native species [26]. Alien plants had not reduced the diversity of native species and had a great contribution to the richness of herbs.…”
Section: Selection Of Dominant Speciesmentioning
confidence: 99%